INFLUENCE OF BIOFERTILIZER ON GROWTH IMPROVEMENT OF AEROBIC RICE - GENOTYPES & A. I. Take-tsaba; A. S. Juraimi; M. R. Yusop; R. Othman; A. Singh (Journal of Animal and Plant Sciences, 2018)
Biofertilizers have emerged as a potential environment friendly inputs that are supplemented for proper plant growth. st Two field experiments were conducted at University Putra Malaysia (UPM) , Selangor, Malaysia during 1 season (May nd to September 2015) and 2 season ( September to December 2015) to evaluate the performance of aerobic rice genotypes under different combinations of bio and chemical fertilizer. The experiment consisted of five (5) biofertilizer -1 combinations (chemical fertilizer recommended rate (CFRR) (150 N; 60 P O 60 K O kg ha ) 100%, biofertilizer 1 ton 2 5; 2 + 75% CFRR, biofertilizer 2 tons + 50% CFRR, biofertilizer 3 tons + 25% CFRR, and biofertilizer 4 tons) and three aerobic rice genotypes (MRIA1, MR219-4 and MR219-9) laid out in a split-plot in randomized complete block design (RCBD) with 3 replicates. Results revealed that application of biofertilizer 1 ton + 75% CFRR produced the highest nd -1 plant height (102.65 cm) and a number of tillers ( 20.38) in the 2 season, the highest grain yield (4.30 t ha ) than the st other biofertilizer treatments in the 1 season. MR219-4 produced the highest number of tillers, leaf area and leaf -1 st photosynthesis rate in both seasons, grain yield ( 5.02 t ha ) in 1 season while MR219-9 produced the highest crop -1 -1 -1 -1 biomass (52.76 g hill ) and crop growth rate (8.00 g hill week ) at 12 WAS, grain yield ( 3.86 t ha ) than the other nd genotypes in the 2 season. The trend in these results indicated that biofertilizer tend to be more effective with limited st chemical fertilizer in the 1 season of low rainfall. These results concluded that 1 ton biofertilizer + 75% CFRR and MR219-4 enhances rice growth and grain yield in aerobic condition. Aerobic rice production system is an innovative
Keywords: rice production; eco-friendly; rice varieties; sustainable agricultural system; chemical fertilizer.